Validating Rat Model of Empathy for Pain: Effects of Pain Expressions in Social Partners - Li, Chun-Li; Yu, Yang; He, Ting; Wang, Rui-Rui; Geng, Kai-Wen; Du, Rui; Luo, Wen-Jun; Wei, Na; Wang, Xiao-Liang; Wang, Yang; Yang, Yan; Yu, Yao-Qing; et al. (Frontiers in Behavioral Neuroscience, 2018)
Pain can be socially transferred between familiar rats due to empathic responses. To validate rat model of empathy for pain, effects of pain expressions in a cagemate demonstrator (CD) in pain on empathic pain responses in a naïve cagemate observer (CO) after 30 min priming dyadic social interactions (PDSI) were evaluated. The CD rats were prepared with four pain models: bee venom (BV), formalin, complete Freund’s adjuvant (CFA) and spared nerve injury (SNI). Both BV and formalin tests are characterized by displayable and eye-identifiable spontaneous pain-related behaviors (SPRB) immediately after treatment, while CFA and SNI models are characterized by delayed occurrence of evoked pain hypersensitivity but with less eye-identifiable SPRB. After 30 min PDSI with a CD immediately after BV and formalin, respectively, the empathic mechanical pain hypersensitivity (EMPH) could be identified at both hind paws in CO rats. The BV- or formalin-induced EMPH in CO rats lasted for 4-5 h until full recovery. However, EMPH failed to develop in CO after socially interacting with a CD immediately after CFA, or 2 h after BV when SPRB completely disappeared. The CO’s EMPH was partially relieved when socially interacting with an analgecized CD whose SPRB had been significantly suppressed. Moreover, repeated exposures to a CD in pain could enhance EMPH in CO. Finally, social transfer of pain hypersensitivity was also identified in CO who was being co-housed in pairs with a conspecific treated with CFA or SNI. The results suggest that development of EMPH in CO rats would be determined not only by extent of familiarity but also by visually identifiable pain expressions in the social partners during short period of PDSI. However, the visually unidentifiable pain can also be transferred to naïve cagemate when being co-housed in pairs with a distressed conspecific. In summary, the vicariously social contagion of pain between familiar rats is dependent upon not only expressions of pain in social partners but also the time that dyads spent in social communications. The rat model of empathy for pain is a highly stable, reproducible and valid model for studying the neural mechanisms of empathy in lower animals.